Effective Online Lecturing in Islamic Business School During a New Normal Era - Rosana Eri Puspita; Saifudin Saifudin; Imanda Firmantyas Pertiwi; Puput Yanita Senja (Universitas Negeri Malang, 2020)
The purpose of this study was to assess platform preservation in online learning based on subject type and skills to be achieved. A challenge in the new normal era that requires online learning, but internet access is still considered expensive to reach financially. The new in this research is a topic that examines online learning for Islamic business schools under the ministry of religion, which, of course, has different characteristics from other business schools in Indonesia. Research Methods is using a mixed-method. Descriptive statistics using 86 respondents were used to explore the right platform to improve competence. Qualitative methods are used to find out the reasons for the preference for platforms and explore the problems that exist in using learning platforms. The use of digital platforms as online learning media in Islamic business schools needs to pay attention to the conditions of the ability to access the internet and gadgets, interactions, features that help to learn, and human factors. Necessary to collaborate with several learning media according to the needs and learning objectives.